Improved drug safety through intensive pharmacovigilance in hospitalized pediatric patients - Alan O. Vázquez-Alvarez; Lorena Michele Brennan-Bourdon; Ana Rosa Rincón-Sánchez; María Cristina Islas-Carbajal; Selene G. Huerta-Olvera (BMC, 2017)
Abstract Background The aim of this study was to detect and analyze Adverse Drug Reactions (ADRs) through Intensive Pharmacovigilance (IPV) in hospitalized pediatric patients to improve drug safety. Methods A prospective 6-month cross-sectional study was performed in the pediatric service of a regional hospital in Mexico in order to assess hospitalized children from 1 day to 18 years old. The inclusion criteria were: both genders, all hospitalization causes, and at least one prescribed medication (indistinct drug group). Notifications were performed through medical visits, phone calls, or spontaneous reports. ADR suspicions were assessed with severity scales: Naranjo algorithm, Schumock & Thornton and Hartwig and Siegel. Results From a total of 1083 hospital admissions, 19 ADRs were recorded. The average age of patients in years was 7.2 (±5.9). The causality assessment in this study showed that most of the ADRs were probable (68.4%) and 4 certain (8.2%); causality was mainly attributed to antibiotics (AB) and an antiepileptic drug. We found a relationship of AB with ADRs (p < 0.05) with an increased risk at the third day of prescription (p < 0.05). The average severity was level 2 and 21% were classified as "preventable". Lastly, an increase in hospital stay associated with ADRs (p < 0.05) and with concomitant medications (p < 0.05), was also found. The most severe ADRs were hemolysis and toxic epidermal necrolysis. Conclusions IPV was an effective tool for ADR prevention, detection, and treatment in hospitalized patients. The intensive monitoring approach in pharmacovigilance amplifies ADR detection and this translates into the improvement of drug safety in children.